2021
DOI: 10.1080/21505594.2021.1948277
|View full text |Cite
|
Sign up to set email alerts
|

“Core” RxLR effectors in phytopathogenic oomycetes: A promising way to breeding for durable resistance in plants?

Abstract: Phytopathogenic oomycetes are known to successfully infect their hosts due to their ability to secrete effector proteins. Of interest to many researchers are effectors with the N-terminal RxLR motif (Arginine-any amino acid-Leucine-Arginine). Owing to advances in genome sequencing, we can now comprehend the high level of diversity among oomycete effectors, and similarly, their conservation within and among species referred to here as "core" RxLR effectors (CREs). Currently, there is a considerable number of CR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 178 publications
(260 reference statements)
0
22
0
Order By: Relevance
“…The standard effector prediction pipeline ( Chepsergon et al, 2021 ) was used to predict the effectors. The number of proteins retained in each step is shown in Supplementary Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The standard effector prediction pipeline ( Chepsergon et al, 2021 ) was used to predict the effectors. The number of proteins retained in each step is shown in Supplementary Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…These 71 core effectors probably have a more generalized and host-independent function, such as suppressing plant immunity ( 49 , 69 , 70 ). Since core effectors have the potential to target conserved plant proteins and processes ( 17 , 71 ), they can be harnessed in breeding for durable as well as broad-spectrum resistance in plants ( 43 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although several conserved or “core” RxLR effectors (CRE) of oomycetes have been identified, only a few of these have been functionally characterized, hence making it difficult to have a consensus on the term CREs. In a recent review, CREs were defined as effectors that are conserved among strains of either a pathogen or different pathogen species, with the potential of playing a virulence role during infection process ( 43 ). These effectors are of importance since they are potential targets for breeding for durable resistance in plants ( 44 , 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…This motif is implicated in translocation of the pathogen proteins into host cells 78 , 79 . Interestingly, signal peptide-lacking RxLR effector proteins have been shown to be secreted unconventionally 63 , 80 . In the past, there has been limited genetic information for PPNs, and initial scans of PPN genomes concluded that there were no effectors with RxLR or similar translocation motifs 81 , 82 .…”
Section: Discussionmentioning
confidence: 99%